A review of 50 cases of bath-related headache: clinical features and possible diagnostic criteria - Raimundo Pereira Silva-Néto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To describe clinical features and possible diagnostic criteria of the 50 bath-related headache (BRH) cases that have been published in the literature to date. Methods: Based on a literature search in the major medical databases, we analyzed all case reports or case series on BRH that were published between 2000 and 2017. Results: We describe 48 women and two men diagnosed with BRH. Of these 50 patients, 90% were from Asian countries. The average age was 49.3 years. There was an association of BRH with migraine (28%), tension-type headache (12%) and cold stimulus headache (4%). Headache was bilaterally localized, had an explosive or pulsating quality and a severe intensity. The pain lasted from five minutes to four days. Associated manifestations were nausea, vomiting, photophobia or phonophobia. There was a good therapeutic response with nimodipine and when avoiding a hot bath. Conclusions: Bath-related headache is a benign headache that is not associated with a structural lesion.